George R. Donnan, Annotated Code of Criminal Procedure and Penal Code of the State of New York 298, ch. 375 (4th ed. 1885) - (:unkn) unknown (My University, 1885)
Ch. 375, § 1: No person under the age of eighteen years shall carry or have in his possession in any public street, highway or place in any of the cities of this state, any pistol or other firearms of any kind, and no person shall in such cities sell or give any pistol or other fire-arms to any person under such age
Keywords: POSSESSION - MINORS